Cover Feature: CaII, YbII and SmII Bis(Amido) Complexes Coordinated by NHC Ligands: Efficient Catalysts for Highly Regio‐ and Chemoselective Consecutive Hydrophosphinations with PH3 (Chem. Eur. J. 2/2019). Issue 2 (13th December 2018) - Lapshin, Ivan V.; Basalov, Ivan V.; Lyssenko, Konstantin A.; Cherkasov, Anton V.; Trifonov, Alexander A.
Abstract : The first example of intermolecular highly regio‐ and chemoselective hydrophosphination of olefins and acetylenes with PH3 catalyzed by Ca II, Yb II, and Sm II bis‐(amido) complexes coordinated by NHC ligands is described. The molecules of styrene, phosphine, and primary, secondary, and tertiary phosphines are symbolically depicted in the form of the puppets driven by a green catalyst controlling the chemoselectivity of the hydrophosphination process. More information can be found in the Communication by A. A. Trifonov et al. onpage 459 .